The first case report of Enterococcus gallinarum meningitis in neonate: A literature review. Issue 7 (February 2018) - Li, Xiaoquan; Fan, Shujuan; Lin, Xiaojie; Liu, Li; Zheng, Jie; Zhou, Xihui; Heep, Axel
Abstract: Rationale: Enterococcus gallinarum meningitis (EGM) is rarely found in normal adults and even rarer in children. To our knowledge, EGM in neonate has not been reported previously. Patients concerns: Here we reported the first case of EGM in neonate. Prolonged fever was the only manifestation for the case after admission. Diagnoses: Cerebrospinal fluid cultures showed that the isolate was Enterococcus gallinarum and sensitive to linezolid. Interventions: Ceftriaxone, beta lactam type, and vancomycin were used respectively, but not effective. Outcomes: The temperature went down to normal after linezolid was used and the baby was discharged in good condition in the end. Lessons: This case indicated that EGM could also occur in neonate and fever could be the only obvious manifestation. Thus, the effective antibiotics and adequate duration are very important and linezolid is a potential good choice, especially for vancomycin-resistant patients.